A Review: Parameters Affecting The PVT Collector Performance On The Thermal, Electrical, And Overall Efficiency Of PVT System - Abdullah, Amira Lateef; Misha, Suhaimi; Tamaldin, Noreffendy; Mohd Rosli, Mohd Afzanizam; Sachit, Fadhil Abdulameer (Penerbit Akademia Baru, 2019)
PVT solar systems are recently emerging solar technology that allows the simultaneous conversion of solar energy into both electricity and heat. The aim of these systems PVT is to improve the electrical efficiency with the cooling system by reducing the temperature of the cell. The performance of PV is reduced with the increase in temperature and use under the advice the absorber collector takes in the excess heat underneath the PV and transfers the heat through the working fluid such as water. The harvested heat is used for low-temperature applications such as domestic hot water supply, water preheating, and space heating. In this paper, the effects of the major control parameters on the thermal and electrical performance of PVT collectors are compiled and reviewed. Figures and tables are provided to give an overall picture of how PVT performance could be improved in terms of these parameters. Although investigators understand the effects of different parameters, the improvement of PVT performance by optimizing these parameters has not been fully realized.